The Bécassine albums: from cultural history to classicization - Messonnier, Laurence (Ondina - Ondine, 2023)
Classified among the heritage comics appearing on the reading lists of cycle 3 of primary school, Bécassine pendant la Guerre poses the double problem of the generic serialization (album / comic) and the qualification (heritage / classic) of the work. This duality will be examined from the Bécassine war albums published between 1913 and 1919 in a specific context and cotext: this article examines how the passage from the soap opera in La Semaine de Suzette to the album contributed to their classicization. The process of editorial disclosure is at the heart of the phenomenon, as is the warlike context that has made the heroine a patriotic icon. The canonical, literary, iconographic and educational referents contribute to classical edification. In addition, the “childish periculture” which surrounds the publication of Bécassine's albums contributes to their classicization through the transmediality and the university studies about them.Key words : Bécassine, heritage, transmediality, childish periculture, litterary genre.